Probióticos na ração de frangos de corte e sua influência no Ph do ingluvio e na microbiota intestinal - Frezza, Andréa Leão Carneiro (2008)
In 2006, a ban on the use of antibiotics that promote growth in broilers resulted in the need to evaluate and provide substitutes. One of the most viable alternatives, that does not leave traces in meat destined for human consumption and that does not affect human wellbeing, is probiotics. The objective of this study is to evaluate the use of commercially produced probiotics in the production of broilers at different ages. Evaluations were made of change in the pH level of the crop, enterobacterial count, the Clostridium reducer count in the caecum, as well as indices of weight gain, feed consumption, disease, mortality and the uniformity of the flock. The research involved 120 birds (60 in the test group and 60 in the control group) Coob Vantress, housed in cages with tagged identification. The birds in the test group received feed with pro-biotic supplement from the time they were caged at twenty eight days of age. The control group was given the same feed without the probiotic supplement. At 12, 18, 23 and 28 days of age broilers were randomly selected from each group (the test as well as the control group) for analysis. Birds were weighed and examined clinically with notation of mortality and uniformity of development. On the specified days the quantity of feed given to the birds was also weighed. They were then slaughtered and the pH of the crop measured. The intestines were removed and samples of the caecal contents were obtained from groups of four birds in order to quantify the Clostridium sulfite reducers and levels of Enterobacteria. Results from both the control and the test groups were compared using Student s t test. Significant differences were identified in the pH measurements of the crop (p<.05), at the ages of one, seven and 18 days. However at 12, 23 and 28 days there were no differences (p>.05). In spite of the discovery that at all ages the test birds had higher weight gains, there were no significant differences in weight (p≥.05) between the two groups. There were also no significant differences in feed consumption, disease or mortality among the groups studied. The test group presented higher uniformity only at 7 days of age (p<.05). There was no statistical difference in the Clostridium sulfite reducer count. The enterobacterial count, however, was higher (p<.05) in the birds that did not receive supplement at seven, 18 and 28 days, suggesting greater efficiency of the probiotic supplement in the animals that had received the supplemented feed. The lower pH of the crop observed in broilers receiving supplement is desirable and may have contributed to a lower rate of colonization of enterobacteria. Although no statistically significant differences (p>.05) were identified between the two groups examined, it is believed that if probiotic supplement were adopted on a large scale, the results from this study could mean an increase in revenue since there were, in every phase, greater weight gains among those receiving supplement, even though they received the same amount of feed as the birds of the control group.